MANAGEMENT OF SCABIES IN ISLAMIC BOARDING SCHOOLS: DEVELOPMENT OF EARLY DETECTION CADRES WITHIN THE TAHTUL YAMAN COMMUNITY HEALTH CENTER AREA, JAMBI CITY, 2024 - Hanina; Fitriyanti, Fitriyanti; Lipinwati; Hasna Dewi; Ahmad Syauqy; Attiya Istarini; Ivo Amrina Rasyada (Universitas Jambi, 2025)
ABSTRACT Scabies is a skin disease that is often found in Indonesia caused by Sarcoptes scabei. The prevalence of scabies in Islamic boarding school environments in Jambi is around 4.9%. Sandra Widaty et al. from the Faculty of Medicine, University of Indonesia, have developed a Deskab (Early Detection of Scabies) form that can be used by ordinary people (cadres) very easily, and the results are relatively similar to those carried out by medical personnel. The method is to present cadres and resource persons, conduct a pretest, provide scabies material, posttest, and training on how to directly apply the Deskab form by cadres and be assessed by a doctor. There were 18 participants from four Islamic boarding schools. The majority of participants were male (67%) and adults (19-59 years) (67%). The average pretest and posttest score was 79.64 (80%) and 83.78 (83%). The average score for the Deskab results is 95.12 (95%), and all cadres have a score above 79. All cadres are declared to have passed and are expected to be able to carry out early detection screening on santri so that efforts to control scabies in the work area of the Tahtul Yaman Health Center can be realized as planned. Keywords: scabies, Deskab, cadre, boarding school